Wheat yield and soil physicochemical properties through mineral nitrogen and vermicompost application in Lasta district, North Ethiopia - Melak, Ewunetie; Molla, Eyayu; Feyisa, Tesfaye; Sebnie, Workat; Shitaw, Mamaru; Sida, Tesfaye Shiferaw (Nature Publishing Group, 2025)
Ethiopia’s soils are losing essential nutrients and organic matter, causing a drop in agricultural output. This experiment was therefore conducted to evaluate the effect of combining mineral nitrogen (N) and vermicompost (VC) on bread wheat yield and soil physicochemical properties in the Lasta district. During the 2023 cropping season, the trial employed a factorial design with varying levels of N (0%, 50%, 75%, and 100% of recommended) and VC (0%, 50%, and 100% equivalent to N) on a farmer’s field. The soil samples were analyzed before and after treatment, and the data were analyzed using R software. The results indicated that the total N (TN) (0.131 ± 0.01%) and available phosphorus (Av. P) (22.97 ± 0.05) were recorded from 100% VC, the highest organic carbon (OC) (1.79 ± 0.01%) and CEC (36.8 ± 1.0 cmol+/kg) of the soil were recorded for the combined N and VC application, whereas the lowest TN (0.107 ± 0.01%) Av. P (19.17 ± 0.21), OC (1.05 ± 0.01) and CEC (23.37 ± 1.26) were recorded from the control. The highest grain (3955.33 ± 49.22 kg ha−1) and biomass (9.30 ± 0.1 t ha−1) yields were obtained with full N and VC application, while the lowest were observed in the control. Economic analysis revealed that applying fully recommended N with 100% VC as the N equivalent led to the highest net profit (290088.91 ETB) and acceptable marginal rate of return (1491.24%). It is recommended that farmers adopt 100% of the recommended N with 100% VC equivalence for optimal yields. Further research across diverse locations and years is suggested to validate and understand the residual effects on soil and yield improvements.